Network Centric Warfare dan Perang Asimetris di Afghanistan - Rahmani, Aziz (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2018)
The development of information technology in the world in the last few decades has made the United States (US) develop a military doctrine based on information technology called “warfare network-centric”. When the US invades Afghanistan as part of the global war against terrorism the doctrine of “network-centric warfare” is tested to overcome the conditions of asymmetrical warfare in Afghanistan with the ability to superior information and the use of force in use that can compensate for Taliban fighting and Al-Qaeda is organized by not being hierarchically structured. In conditions of balanced strategic interaction in the conditions of asymmetrical warfare, the US should be able to neutralize Al-Qaeda and the Taliban easily and quickly but the disparities that occur in asymmetric warfare in Afghanistan not only in military strength but also in status, ideological and structural disparities the aim of military operations in Afghanistan has not been fully achieved by the US and has made the war last long.